2018
DOI: 10.1016/j.pt.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Parasites at Risk – Insights from an Endangered Marsupial

Abstract: Parasites are the most abundant form of life on earth and are vital components of ecosystem health. Yet, it is only relatively recently that attention has been given to the risks of extinction that parasites face when their hosts, particularly wildlife, are endangered. In such circumstances, parasites that are host-specific with complicated life cycles are most at risk. Such extinction/coextinction events have been poorly documented, principally because of the difficulties of following such extinction processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…Uncovering factors influencing parasite community assembly is important for predicting disease emergence, outcomes of reintroduction programmes and risks of host–parasite co‐extinction (Agosta et al, ; Lafferty, ; Moens & Pérez‐Tris, ; Thompson et al, ; Viggers et al, ). My global analysis of avian haemosporidian communities identified hotspots of diversity and uncovered consistent variation in biogeographical structure among parasite genera.…”
Section: Discussionmentioning
confidence: 99%
“…Uncovering factors influencing parasite community assembly is important for predicting disease emergence, outcomes of reintroduction programmes and risks of host–parasite co‐extinction (Agosta et al, ; Lafferty, ; Moens & Pérez‐Tris, ; Thompson et al, ; Viggers et al, ). My global analysis of avian haemosporidian communities identified hotspots of diversity and uncovered consistent variation in biogeographical structure among parasite genera.…”
Section: Discussionmentioning
confidence: 99%
“…Given the increased recent interest in conserving parasites, as well as their hosts, as integral components of biodiversity, the loss of parasite species during translocations represents an important risk that needs consideration in translocation protocols. Thompson et al (2018) provided a comprehensive list of woylie parasites and identified six species that appear to be host-specific and are in danger of extinction. Given that we identified three of these six species ( Ixodes woyliei , Eimeria woyliei and Potoroxyuris keninupensis ) plus a novel undescribed species of cestode during this study (Northover et al, unpublished data) and woylies are the most commonly translocated species in Australia (Morris et al, 2015), the consequences of host-specific parasite extinction require careful deliberation.…”
Section: Discussionmentioning
confidence: 99%
“…For woylies, more research is needed to understand the site-level drivers of parasite dynamics. Second, with increasing recognition of the intrinsic biodiversity value of parasites (Colwell et al, 2012; Thompson et al, 2018), the potential loss of host-parasite associations should be a serious consideration when planning fauna translocations. Finally, antiparasitic drugs should be applied prior to translocation only where there is a clear rationale for their use; field studies that examine the response of parasites following experimental manipulation are required to provide such justification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the dangers of local transmission of Trypanosoma cruzi in Australia should not be dismissed, given its emergence in the USA and involvement of native vectors. It should not be necessary to wait until a species is in danger of extinction before doing this [ 57 ], but such studies should be ongoing and the importance of doing so recognised by appropriate conservation agencies and granting agencies.…”
Section: Concluding Commentsmentioning
confidence: 99%